KONSTUKSI PEMAKNAAAN MASYARAKAT PRIBUMI: MAKNA MASYARAKAT PENDATANG BAGI ANGGOTA MASYARAKAT PRIBUMI DESA NEROKTOG KECAMATAN PINANG KOTA TANGERANG - Een Irianti (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2019)
This article examines the meaning of immigrant society for members of indigenous communities by taking the case in the village of Neroktog, Pinang Subdistrict, Tangerang City, using descriptive qualitative assessment, this research is carried out by exploring the phenomenon construction the reality of social interactions that occur between indigenous and migrant communities. The results show that the meaning of self, the meaning of information and the meaning of immigrants are described differently by each member of the indigenous community. Differences in perceptions that occur indicate that experience, attitudes, power, information, the meaning of self become a construction space where attendance is interpreted by indigenous people.